2021
DOI: 10.1088/1361-6463/ac2383
|View full text |Cite
|
Sign up to set email alerts
|

On the fabrication of one-dimensional magnetophotonic crystals from various oxides and metal–organic decomposition-made Bi0.5Y2.5Fe5O12

Abstract: We demonstrate an approach for the fabrication of one-dimensional magnetophotonic crystals (1D MPCs) that are composed of electron beam evaporation-deposited Bragg mirrors (BMs) and a bismuth-substituted yttrium iron garnet layer made by metal-organic decomposition. Since such a garnet layer is crystallized at high temperatures, changes in structural and optical properties of BMs caused by annealing are studied. By subjecting single layers of SiO 2 , HfO 2 , ZrO 2 , and Ta 2 O 5 to annealing, we found changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The final dodecane solution with a Bi/Y/Fe ratio of 1.5:1.5:5 was then filtered through a 0.22 μm syringe filter and was stored under cool and dry conditions. A single 500 nm-thick metal–organic layer is transformed into a 30–50 nm-thick oxide layer upon heating as reported earlier . Ten 500 nm-thick metal–organic layers were repeatedly spin-coated on the UV-grade fused silica substrate and annealed in air at 400 °C for 30 min to obtain 360 nm-thick oxide film for subsequent irradiation by femtosecond laser pulses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final dodecane solution with a Bi/Y/Fe ratio of 1.5:1.5:5 was then filtered through a 0.22 μm syringe filter and was stored under cool and dry conditions. A single 500 nm-thick metal–organic layer is transformed into a 30–50 nm-thick oxide layer upon heating as reported earlier . Ten 500 nm-thick metal–organic layers were repeatedly spin-coated on the UV-grade fused silica substrate and annealed in air at 400 °C for 30 min to obtain 360 nm-thick oxide film for subsequent irradiation by femtosecond laser pulses.…”
Section: Methodsmentioning
confidence: 99%
“…High-temperature annealing required for Bi/YIG crystallization limits potential applications of this material for optical applications. For example, the process may result in the decrease in a magnetophotonic crystal performance through occurrence of cracks and growth of microcrystals in layers composing Bragg mirrors. , The same annealing also restricts integration of magneto-optical rare-earth-substituted yttrium iron garnets on nongarnet substrates for photonic integrated circuits. Thus, to overcome this issue, new approaches of Bi/YIG crystallization have to be developed. Jeffery et al suggested lowering temperature of bismuth iron garnet crystallization by approximately 100 °C below the temperature required to achieve crystallization via conventional thermal annealing using capacitively coupled oxygen plasmas .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation